Field Trip Learning Method Based on the Teaching Example of the Lord Jesus and its Implementation in Christian Religious Education - Zega, Darmin Usman (Asian Journal of Philosophy and Religion, 2023)
The field trip learning method which is based on the exemplary teachings of the Lord Jesus Christ combines the principles of effective learning with spiritual values. The teachings of the Lord Jesus can be adapted into a field trip learning context to create a holistic and memorable learning experience. The aim of the field trip learning method is first, to provide students with an interesting experience in the learning process. Second, it gives a pleasant impression with an open environment. Third, attract students' attention to get to know historical, cultural and natural places. By developing field trip methods in children's learning processes, values such as cooperation, empathy and understanding of diversity will be fostered. In the application process, field trip learning principles based on the example of Jesus Christ emphasize direct experience, collaborative learning, and the development of a deep understanding of local culture and heritage. The teachings of the Lord Jesus Christ were renowned for their approach that was motivating, inclusive, and suited to the needs of His disciples. This approach involves the use of stories, parables, and real-life examples to strengthen understanding and application of moral and spiritual principles in everyday life.